Neuroimaging in Pregnant Women - Chansakul, Thanissara; Young, Geoffrey S. (Seminars in Neurology, 2017)
Choosing the most appropriate diagnostic neuroimaging study for a pregnant woman involves assessing the pretest likelihood of serious treatable neurologic disease, the diagnostic utility of various available computed tomography (CT) and magnetic resonance (MR) modalities, and the risks of each. Of these three elements—pretest differential diagnosis, utility of MRI and CT, and risks of MR and CT—the risk component is perhaps the least well understood by most physicians. We provide a basic review of the intrinsic risks of MRI and CT, particularly radiation biology and radiation safety, as well as the risks pertaining to the use of contrast agents, to reduce provider confusion and anxiety and improve quality, safety, and efficiency of neuroimaging diagnosis in pregnant patients. We believe that a better understanding of the associated very low risks with mother and fetus will reassure the reader that CT remains the most appropriate tool for initial rapid diagnosis of acute neurological conditions in pregnancy and that in urgent situations CT should not be withheld or delayed due to exaggerated concern about radiation. Noncontrast MRI, while not without risk, is generally considered safe in pregnancy, as no evidence of fetal adverse effects has been demonstrated to date. Iodinated CT contrast agents are likely safer than gadolinium-based MRI contrast agents because of gadolinium accumulation in the amniotic fluid and fetal tissue, although no harmful effects of tissue gadolinium accumulation are known. In most but not all pregnant patients presenting with a new or worsening neurological abnormality, the risks intrinsic to the disease will outweigh the risks of imaging. In an individual patient, the pretest probability of serious treatable disease and acuity of presentation will usually suggest an optimal imaging strategy and choice of test. This optimal strategy will also depend on the immediate availability and level of sophistication of the scanners, software, technologists, and radiologists. As such, the standard of care for imaging in pregnancy requires direct consultation between the referring clinician and radiologist to determine the most appropriate strategy and brief documentation of the resulting consensus risk–benefit assessment.
Keywords: pregnancy; risk–benefit analysis; imaging; radiation biology; radiation safety; contrast agent safety; MRI safety